2022
DOI: 10.1007/s10734-022-00931-8
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualising international academic mobility in the global knowledge system: towards a new research agenda

Abstract: The cross-border movement of people in higher education has been attracting scholarly attention for decades, but the definition of ‘international academic mobility’ bears ambiguities. This article reviews the literature on international academic mobility published in the journal Higher Education and beyond. By bridging the literature on international academic mobility from higher education studies and other disciplines, this article proposes to redefine international academic mobility, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 154 publications
0
10
0
Order By: Relevance
“…The internationalization of institutions is a transformative process in global perspective (Bombita & Dicolen, 2020). Through IMP, students gain new perspectives on country comparisons (Shen et al, 2022). They bring home experiences that involve not only academic aspects but also character aspects in understanding the habits, cultures, and communication styles of citizens in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…The internationalization of institutions is a transformative process in global perspective (Bombita & Dicolen, 2020). Through IMP, students gain new perspectives on country comparisons (Shen et al, 2022). They bring home experiences that involve not only academic aspects but also character aspects in understanding the habits, cultures, and communication styles of citizens in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars with mobility experiences often have greater output and stronger influence in the scientific research community; their papers are cited more frequently [32], and they tend to publish articles in journals with higher average impact factors, so the quality of scientific research output is higher [33]. More recent studies can be found in related articles [34][35][36][37]. Considering the literature, this paper proposes the following hypotheses: H1: Scholars with mobility experiences publish more papers.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Institutions from these countries have effectively integrated themselves into global academic networks partially through successful policies for internationalization of graduate and research programs, well-funded by universities, governments and companies [ 67 ]. For example, Nanyang Technical University, the Chinese University of Hong Kong, and the Korea Advanced Institute of Science and Technology (KAIST) in Seoul are cases of institutions who have overcome the one-way road of talent departure [ 68 ]. This can be viewed as a significant outcome of past investments in R&D capabilities within some emerging economies.…”
Section: Autonomous Experimentation In Emerging Economiesmentioning
confidence: 99%